Synthesis and structural diversity of d10 metal coordination polymers constructed from new semi-rigid bis(3-methyl-1H-pyrazole-4-carboxylic acid)alkane ligands. (30th May 2017) - Cheng, Meiling; Wang, Qinghua; Bao, Jinting; Wu, Yujuan; Sun, Lin; Yang, Bingxin; Liu, Qi
Abstract : Three isomeric ligands, and four d 10 metal CPs were synthesized, varying from 1D to 2D, together with achirality to chirality variation. Abstract : Three isomeric bis(3-methyl-1 H -pyrazole-4-carboxylic acid)alkane ligands (H2 L 1, H2 L 2 andH2 L 3 ) were prepared via a two-step process from ethyl 3-methyl-1 H -pyrazole-4-carboxylate (1 ). They were introduced as bridging ligands to assemble with Zn(ii ) and Cd(ii ) ions, and two chiral coordination polymers [Zn(L 1 )(DMF)(H2 O)] n (3a and3b ), [Cd(L 1 )(H2 O)] n · n H2 O (5 ) and two achiral coordination polymers [Zn(L 1 )(H2 O)2 ] n · n H2 O (4 ), [Cd(L 2 )(H2 O)] n ·2 n H2 O· n EtOH (6 ) were obtained. (L 1 ) 2− adopts a trans -conformation in3, leading to the formation of 1D coordination chains, and the 2D coordination layers in4–6 are constructed from (L 1 ) 2− /(L 2 ) 2− anions in a cis -conformation. Notably, the structures of3a and3b exhibit an H-bonded chiral 2D network, featuring a right-handed 3-fold helix in3a, while a left-handed 3-fold helix in3b . Compound5 possesses a 3D supramolecular network with homochiral left-handed helical chains, whose chirality is due solely to the hydrogen bonds. The chiral nature of enantioenriched3a produced by diffusion crystallization was confirmed by solid-state CD spectroscopy. The thermal and luminescence properties of3–6 in the solid state have also been investigated.